Precautionary and Liquidity Line : Operational Guidance Note. (Policy Papers; Policy Paper, 2015)
This note provides general guidance on the use of the Precautionary and Liquidity Line (PLL). After an overview of the instrument, explaining its specific nature, the operational issues are grouped into five areas: an outline of the process and specific steps that need to be followed if a member expresses interest in an arrangement; guidance on access, phasing, and purchases; guidance on determining qualification of a member and appropriate ex-post conditionality; and a guide to the semi-annual review process.